Open-access bioarchaeology resources for the Eastern Mediterranean and Middle East (EMME) - Mardini, Mahmoud; Polyzou, Stella; Lato, Lentia (My University, 2025)
Abstract: Bioarchaeological data can provide long-term perspectives on humans’ complex biosocial nature and interactions with their environments; this includes, among others, issues of animal exploitation, landscape transformation, agricultural practices, and human responses to socio-political and environmental changes. Such perspectives require multiscalar studies that span different temporal and spatial contexts; however, the majority of relevant research in the Eastern Mediterranean and Middle East (EMME) focuses on case studies, with fewer large-scale comparative analyses and meta-analyses. In recent years, multiple open-access databases and tools have been developed to promote bioarchaeological research at broader spatial and analytical scales in the Eastern Mediterranean and Middle East (EMME) region. These resources include Bi(bli)oArch, an open-access bibliographic database for human bioarchaeological studies from the EMME, and SrIsoMed, an openaccess database of published strontium isotopic values across the Mediterranean. In addition, following the Bi(bli)oArch model, ZooBi(bli)oArch and PlantBi(bli)oArch have been established as bibliographic databases for zooarchaeological and archaeobotanical studies in the EMME. More recently, MetaBioarch has been introduced as a database compiling published osteoarchaeological, zooarchaeological, and archaeobotanical data from Hellenistic and Roman contexts in the Central and Eastern Mediterranean, supporting largescale comparative studies and meta-analyses. To promote standardized data recording and facilitate data sharing, STARC OSTEOARCH was created as a tool for human skeletal data collection. Given the centrality of skeletal sex and age-at-death estimation in human skeletal analyses, AgeEst and Sex-Est were developed as open-access web applications employing machine learning approaches. A separate set of resources was also produced to encourage optimal methodologies and best practices in archaeological science across various sub-fields, particularly in relation to the excavation and analysis of human skeletal remains. In addition, freely available educational guides, such as Archaeological Science Classroom Activities and Bare Bones: Our ancestors’ bones have a lot to say, were produced to promote archaeological sciences to the general public.
Keywords: human osteoarchaeology; zooarchaeology; archaeobotany; isotopes